Voorbereiding vir aftrede en bejaardheid - A. Gerretsen (Curationis, 1982)
The number of retired persons in the community is increasing steadily. Retirement is a relatively modern concept and the problems associated with it are not yet fully understood. People should prepare themselves for retirement to ensure that it will be a creative and satisfying time of life. There are currently a number of programmes to prepare workers for retirement such as the one offered by the Retirement Association. The nurse has a role in motivating members of the community to plan for retirement and should include this topic in health education, using a non-directive approach. She can also help to create a more positive attitude towards retirement and retired people among the younger members of the community.